Lateral Approach for Regenerative Treatment of Intrabony Defects Associated With an Edentulous Alveolar Ridge: A Prospective Case Series - Hromčík, Filip; Halusková, Adéla; Hollá, Lydie Izakovičová (Clinical and experimental dental research, 2025)
OBJECTIVES: This case series evaluated the clinical efficacy of the novel "lateral approach" combined with an enamel matrix derivative (EMD) and bone grafting in the regenerative surgical treatment of intrabony defects associated with an edentulous ridge. MATERIAL AND METHODS: The innovative flap, called the "lateral approach," is explicitly designed for regeneration of unchallenged isolated intrabony defects associated with edentulous alveolar ridges. The flap is defined by a curved vertical incision on the buccal side opposite the treated defect and a sulcular incision on the buccal and defect-associated sides, promoting uneventful healing and regeneration while minimizing complications. Seven intrabony defects (one per patient) distal to the lower second molar were treated using the "lateral approach" combined with EMD and grafting with deproteinized bovine bone mineral. The primary outcome was clinical attachment level (CAL) change. As additional parameters, pocket probing depth (PPD) reduction and complication rate were analyzed. All the outcomes were assessed 6 months post-surgery and compared with the baseline values. RESULTS: Primary wound healing occurred in 100% of cases, and no complications were reported. At the 6-month re-evaluation, the initial median CAL of 6 mm (interquartile range 5-8 mm) was reduced to 3 mm (3-5 mm). The corresponding median PPD was reduced from 6 mm (IQR 6-8 mm) to 4 mm (IQR 3-5 mm). These differences were statistically significant (p < 0.05). CONCLUSIONS: The "lateral approach" is a technique for the surgical treatment of intrabony defects associated with the edentulous ridge. Within the limitations of the study, this method seems to be suitable for distal intrabony defects in the lower second molars, which frequently develop after third molar extraction.
Keywords: hojení ran; řízená tkáňová regenerace parodontu; lidé; Middle Aged; výsledek terapie; Adult; Wound Healing; prospektivní studie; Female; transplantace kostí; augmentace alveolárního výběžku; Bone Transplantation; Surgical Flaps; proteiny zubní skloviny; resorpce alveolární kosti; Humans; Prospective Studies; regenerace kostí; lidé středního věku; kostní náhrady; mužské pohlaví; ženské pohlaví; čelist bezzubá; Alveolar Bone Loss; Treatment Outcome; Male; Aged; Bone Substitutes; Dental Enamel Proteins; Jaw, Edentulous; dospělí; Alveolar Ridge Augmentation; Guided Tissue Regeneration, Periodontal; Bone Regeneration; chirurgické laloky; senioři